The finance of international trade : notebook and document - Watson, Alasdair (London : Institute of Bankers, 1976)
Provides a sound understanding of international trade finance including the foreign exchange and support services provided for exporters, importers and merchants.
Includes index.
gp 24/01/2019
Loans
Keywords: International finance